Demand for high-value secondary crops in developing countries: the case of potatoes in Bangladesh and Pakistan - Bouis, Howarth E.; Scott, Gregory J. (International Food Policy Research Institute, 1996)
Secondary crops are of increasing interest to policymakers and planners in developing countries because of a desire to diversify economic activities and because of their proven potential to raise farm incomes and rural employment. To assess this potential, basic information on the demand characteristics for these crops is required. But, given the large number of possible crops to be studied, policy analysts require an estimation procedure that is less data-intensive and time-intensive than standard econometric estimation procedures. In this paper, a relatively new, low-cost procedure, based on demand for food characteristics, is applied, illustrating its usefulness for analysis of demand for potatoes in Bangladesh and Pakistan. In Asia, the potato should not be regarded as a starchy staple whose consumption declines as income increases, but rather as a food with a positive income elasticity. Due to the high calorie cost of potatoes relative to wheat and rice, potatoes are often valued primarily for the variety they contribute to the diet and their taste, rather than for the calories they provide. This means that demand for potatoes should increase with income in the future. However, expansion of demand for potatoes as an alternative food staple is conditional upon the cost per calorie for potatoes approaching that for wheat and rice. Results from Bangladesh for more recent years show that with the rise in potato production, relative prices for potatoes versus wheat fell and per capita consumption of potatoes increased considerably. These findings are consistent with demand parameters generated utilizing the new estimation procedure.